Carney complex: left atrial myxoma in a patient with past pituitary microadenoma and lentiginosis. Issue 6 (24th June 2021) - Spindel, Jeffrey; Mathbout, Mohammad F; Huffman, Travis; Ghafghazi, Shahab
Abstract : The Carney complex (CNC) is a rare autosomal dominant genetic complex that is characterised by multiple neoplasms consisting of neuroendocrine and cardiac tumours, with only 750 cases reported worldwide as of 2017. Cardiac tumours, in the context of the CNC, are of unique importance since the leading causes of death in patients with CNC are cardiac. To prevent sudden cardiac death and embolic events, a difficult diagnosis must be made and postdiagnostic screenings must be regular. We present a case of a 52-year-old man, with a medical history of pituitary microadenoma and facial lentiginosis, who presented with dyspnoea 2 months after suffering a cerebrovascular accident.